Histological comparison of in vitro and in vivo development of peripheral posterior capsule opacification in human donor tissue. (November 2019) - Koch, Camila Ribeiro; D'Antin, Justin Christopher; Tresserra, Francisco; Barraquer, Rafael I.; Michael, Ralph
Abstract: In order to study the mechanisms involved in the development of posterior capsule opacification (PCO) we compared in vivo developed PCO with PCO formed in tissue culture with focus on the periphery of the lens capsule to evaluate lens regeneration potential. We studied three human tissue groups: Cultured lens capsules after mock cataract surgery (n = 6, 30 days), lens capsules from donors that had previously undergone cataract surgery (IOL capsules) (n = 12) and intact lenses (n = 6). All samples were stained with Vimentin, alpha Smooth Muscle Actin, Picro Sirius Red (for collagen) and Paired box protein (Pax6). We found that cultured capsules and less developed IOL capsules consisted mainly of monolayers of mesenchymal cells, while more developed IOL capsules, contained lens epithelial cells (LECs), globular cells and lens fiber cells. Many IOL capsule samples expressed collagen I and III in areas where cells were in contact with the IOL. Pax6 had a similar dispersed distribution in less developed IOL capsules and cultured capsules, while more developed IOL capsules and intact lenses, concentrated Pax6 in LECs at the equatorial lens bow. The similarities between cultured capsules and less developed IOL capsules indicate that our in vitro developed PCO is comparable to early in vivo developed PCO. The similar morphology of more developed IOL capsules and intact lenses seems to indicate an attempt at lens regeneration. Highlights: In vivo developed PCO showed either a fibrotic morphology or a morphology very similar to the intact crystalline lens. In in vivo samples, fibrotic tissue with collagen deposits was only found were tissue was in contact with IOL material.. In vivo developed PCO as well as in vitro developed PCO showed many cells with the potential to develop into lens fibers.